Flexible wearable biosensors from poly (ionic liquid) for real-time signal monitoring - Liu, Yao; Han, Siyu; Gu, Panpan; Wang, Bai; Tian, Shiyan; Xu, Xiaoxu; Yang, Chunmei; Liu, Shujun; Hu, Jianshe (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionModern wearable electronics demand materials that are simultaneously stretchable, conductive, and environmentally robust. Hydrogels meet some of these requirements but dehydrate or freeze easily. To overcome these limitations, we prepared a poly-ionic-liquid (PIL) ionogel that integrates high elasticity with stable ionic conductivity, aiming to enable reliable, skin-compatible strain and biopotential sensing.Methods1-Vinyl-3-butyl-imidazolium hexafluorophosphate and 1-butyl-3-methyl-imidazolium hexafluorophosphate were mixed at optimized mass ratios, followed by N,N’-methylenebis-acrylamide (cross-linker) and Irgacure-2959 (photoinitiator). The homogeneous precursor was UV-cured for 6 min to obtain a PIL ionogel (PIL-1 – PIL-4 series). Structural, thermal, mechanical, rheological, adhesive, and electrical characteristics were analysed by FT-IR, SEM, TGA/DSC, uniaxial tensile testing, rheometry, 90° peel tests, and real-time resistance measurements. Applications were evaluated by attaching the gel to human joints and by recording EMG/ECG signals.ResultsThe UV one-step process yielded a dense multi-cross-linked network that combined covalent and ionic interactions. The optimised sample (PIL-2) showed a fracture stress of ∼390 kPa with 320% elongation, sustaining a 500 g load without failure. It retained mass and softness after 30 days and adhered strongly (up to 90° peel strength >4 N) to glass, metals, and skin—even underwater. Electrical tests gave a gauge factor of 1.94 (0–100%), 3.98 (100–200%), and 4.04 (200–320%), with 400 ms response and 500 ms recovery. The gel monitored finger (30°/90°), wrist, and elbow motions reproducibly, functioned as a bioelectrode capturing stable EMG/ECG with clear PQRST waves, and reliably transmitted Morse code via hand gestures.DiscussionThe solvent-free PIL ionogel couples mechanical toughness, wide-range elasticity, and stable ionic pathways, outperforming water-rich hydrogels in thermal/long-term stability. Its strong, humidity-tolerant adhesion eliminates extra fixatives, while rapid, high-gain strain transduction and low-impedance skin contact enable multimodal biosensing. These attributes position the material for next-generation flexible electronics, real-time health monitoring, and gesture-based human-machine interfaces.